The dragon lanterns : a book about honesty ([Hong Kong] : Time Life Asia, 1997)
"A dishonest man steals two magical dancing lanterns and pretends that he made them himself. When he presents them to the Emperor, his deceit is soon found out and he discovers what happens to people who steal and lie."--Cover.
Keywords: Values -- Juvenile literature; Honesty -- Juvenile literature